2022
DOI: 10.3390/su142214688
|View full text |Cite
|
Sign up to set email alerts
|

Technological Innovation, Risk-Taking and Firm Performance—Empirical Evidence from Chinese Listed Companies

Abstract: Technological innovation can restructure the production factors of enterprises, and it is an important factor for enterprises to meet market demand, improve competitiveness, form long-term competitive advantages and obtain sustainable development. This study focuses on the practical issue of the impact of technology innovation on firm performance. Taking 1166 listed companies in China from 2012 to 2020 as research samples, this study systematically investigates and reveals the impact of technological innovatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 41 publications
0
22
0
1
Order By: Relevance
“…For firms, managerial competence is reflected in the ability to efficiently integrate corporate resources to enhance the efficiency of business operations [5]. Compared with lowlevel managers, high-level managers usually have rich knowledge and experience and can calmly control project risks and make correct decisions through internal control and system reform in a risky state [6], and at the same time, capable managers have more perfect social network relationships and can provide a continuous and stable supply of resources for the enterprise [7], which enables managers to internal and external resources are integrated and optimized, enabling managers to use reliable transaction channels to invest in high-risk projects. Therefore, high competence managers show higher strategic risk-taking ability than mediocre managers in corporate decision making, which will increase the level of corporate risk-taking and thus ensure that risky decisions can be strongly secured and steadily promoted, resulting in more risky and aggressive management in financial investment activities and catalyzing the transformation of the company into a financial one.…”
Section: Theoretical Analysis and Research Hypothesismentioning
confidence: 99%
“…For firms, managerial competence is reflected in the ability to efficiently integrate corporate resources to enhance the efficiency of business operations [5]. Compared with lowlevel managers, high-level managers usually have rich knowledge and experience and can calmly control project risks and make correct decisions through internal control and system reform in a risky state [6], and at the same time, capable managers have more perfect social network relationships and can provide a continuous and stable supply of resources for the enterprise [7], which enables managers to internal and external resources are integrated and optimized, enabling managers to use reliable transaction channels to invest in high-risk projects. Therefore, high competence managers show higher strategic risk-taking ability than mediocre managers in corporate decision making, which will increase the level of corporate risk-taking and thus ensure that risky decisions can be strongly secured and steadily promoted, resulting in more risky and aggressive management in financial investment activities and catalyzing the transformation of the company into a financial one.…”
Section: Theoretical Analysis and Research Hypothesismentioning
confidence: 99%
“…Yang H. C. et al (2021) found that EPU has a positive effect on R&D input and innovation output of family business. The literature holds negative views believes that EPU will increase the bank credit risk and make the enterprise have to face strong financing constraints, thus having obvious inhibitory effect on enterprise technological innovation (Zhang and Feng, 2018). The lack of financing capacity caused by macroeconomic uncertainties will limit the improvement of enterprises' R&D and innovation (Pan and Dong, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Zhang et al [ 2 ] proposed that innovation is the primary productive force for enterprises in the face of external competition and internal sustainable development. Improving the level of enterprise innovation is an effective method for enterprises to effectively cope with uncertainty in the business environment, and it is also an important way for China to move toward high-quality and high-level economic development and enhance its international competitiveness.…”
Section: Introductionmentioning
confidence: 99%